Obszary i etapy badań marketingowych - Ciechomski, Wiesław (Wydział Prawa i Administracji UAM, 1994)
The article is devoted to market research and analyses. In the first part, where areas of market research are described, those pertaining to demand, product, distribution and promotion are distinguished. In the second part the stages of marketing research are described, starting from the problem and research objective definition and ending with the practical application of research results and of the conclusions flowing therefrom. The entire article attempted to stress the importance of complete, up-to-date and reliable information for a company's marketing management.
Areas and stages of marketing research